Cash Transfers and Mayoral Elections: The Case of Sao Paulo's Renda Mínima - Diego Sanches Corrêa (Brazilian Political Science Review, 2015)
Several recently published studies analyze the effects of national conditional cash transfer (CCT) programs, such as the Brazilian Bolsa Família and the Mexican Oportunidades, on presidential elections. Most of them show that these programs boost incumbents' electoral support among the poor. This research note is the first scholarly attempt to investigate this phenomenon at a lower-level unit of a federal state, by assessing the impact of a municipal cash transfer program on a mayoral election. Specifically, it investigates whether Renda Mínima, the cash transfer program of the city of Sao Paulo, affected beneficiaries' electoral behavior in favor of the incumbent candidate in the 2004 mayoral election. This note analyzes survey data from CEBRAP/IBOPE and shows that cash transfers did, indeed, affect beneficiaries' behavior in the predicted direction, but only in cases where they did not benefit from any other CCT program, such as the federal Bolsa Família or the São Paulo state Renda Cidadã. These results suggest that the pro-incumbent effect of CCT programs may be diluted by similar programs launched by governments at other tiers of a federation, even if they are led by the same party.